2007
DOI: 10.5565/rev/catjl.122
|View full text |Cite
|
Sign up to set email alerts
|

Italian allora, French alors: Functions, convergences and divergences

Abstract: The functions, convergences, and divergences of Italian allora and French alors are analyzed in two Italian texts (the Novellino, in Old Italian, and Paso Doble, in Modern Italian) and their French translations. The discourse marker is used differently in the two languages, and the contrastive analysis allows us to better assess those differences, by explicitly quantifying the degree of correspondence, omissions, and non-literal translations. Furthermore, our work confirms the existence of functions which may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
0
7
0
3
Order By: Relevance
“…These corpus-based studies reveal formal, functional and distributional differences within and between languages. For instance, Bazzanella et al (2007) have shown that the Italian-French cognates allora / alors share the same meanings but that these meanings present a different degree of prototypicality, i.e. more or less central vs. peripheral in their category, with the temporal value being more prominent for the Italian DM.…”
Section: Contrastive Fluency: Discourse Markers and Filled Pausesmentioning
confidence: 99%
“…These corpus-based studies reveal formal, functional and distributional differences within and between languages. For instance, Bazzanella et al (2007) have shown that the Italian-French cognates allora / alors share the same meanings but that these meanings present a different degree of prototypicality, i.e. more or less central vs. peripheral in their category, with the temporal value being more prominent for the Italian DM.…”
Section: Contrastive Fluency: Discourse Markers and Filled Pausesmentioning
confidence: 99%
“…In particular, notice that allora 'then, so' is frequently used also by L1 speakers (13%). This result is not unexpected, given the number of functions allora has in Italian (Bazzanella et al 2007;Bazzanella & Borreguero 2011). On the contrary, be' 'well' is never found in the native speakers' linguistic production, nor in the L2 speakers' production before their Erasmus (cf.…”
Section: L1 Clipsmentioning
confidence: 88%
“…These DMs are diciamo (used by BLP 1), ecco (employed by BLP 2), and ma (identified in the writing by BLP 3). In terms of the style conventions of the Italian language, the DMs diciamo, ecco, and ma are deemed to pertain to stylistically neutral DMs (Bazzanella et al 2007). It should be noted that unlike the English DMs used by the participants, for instance, the temporal DM just, there are no DMs that are common to all three participants.…”
Section: The Use Of the Italian Dms By The Participantsmentioning
confidence: 99%
“…By explaining this definition, Heine (2013Heine ( : 1208 argues that in the English language DMs are illustrated by such words and phrases as anyway, however, indeed, I mean, you know, you see, etc. The literature in linguistics (Bazzanella et al 2007;Orsolini 1993;Waltereit 2002) indicates that typical examples of DMs in Italian are allora (translated into English as "then", "therefore"), diciamo ("let's say"), and insomma ("in conclusion", "finally"). In the present case study, DMs are considered to be utterance-initial elements whose use is syntactically independent and sequentially dependent (Maschler and Schiffrin 2015;Schiffrin 1987).…”
Section: Introductionmentioning
confidence: 99%